Upgrading the Functional Potential of Apple Pomace in Value-Added Ingredients with Probiotics - Camelia Cristina Vlad; Bogdan Păcularu-Burada; Aida Mihaela Vasile; Ștefania Adelina Milea; Gabriela-Elena Bahrim; Gabriela Râpeanu; Nicoleta Stănciuc (Antioxidants, 2022)
Emerging customized designs to upgrade the functional potential of freeze-dried apple pomace was used in this study, in order to transform the industrial by-products into ingredients containing probiotics, for a better and healthier food composition. The freeze-dried apple pomace was analyzed for free and bounded phenolic contents, highlighting a significant level of caffeic acid (4978.00 ± 900.00 mg/100 g dry matter (DM)), trans-cinnamic acid (2144.20 ± 37.60 mg/100 g DM) and quercetin 3-β-D-glucoside (236.60 ± 3.12 mg/100 g DM). The pectin extraction yield was approximatively 24%, with a degree of esterification of 37.68 ± 1.74%, and a methoxyl content of 5.58 ± 0.88%. The freeze-dried apple pomace was added in a different ratio as a supplement to cultural medium of Loigolactobacillus bifermentans MIUG BL 16, suggesting a significant prebiotic effect (p < 0.05) at concentration between 1% and 2%. The apple pomace was used to design three freeze-dried ingredients containing probiotic, with a high level of polyphenolic content (6.38 ± 0.14 mg gallic acid equivalents/g DM) and antioxidant activity (42.25 ± 4.58 mMol Trolox/g DM) for the powder containing apple pomace ethanolic extract. When inulin was used as a prebiotic adjuvant, the obtained powder showed a 6 log/g DM viable cell count. The ingredients were added to fermented vegetable soy milk-based products, allowing us to improve the polyphenolic content, antioxidant activity and viable cell counts. The approach designed in this study allowed us to obtain ingredients suitable to add value to food, whereas premises to align with the current circular economy premises, by reintegrating the industrial waste as sources of high added value compounds, are also provided.